Theoretical studies of nitrilotriacetic acid and nitrilotripropionic acid geometries for estimation of the stability of metal complexes by Density Functional Theory - Cukrowski, Ignacy (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2010.